Fuel cell projects for the evil genius - Harper, Gavin D. J. (New York : McGraw-Hill, 2008)
A fun and environmentally-aware project book focusing on fuel cells--technologies that generate electrical power whose only waste output is water. Includes concepts important to fuel cell technology, how to build a simple fuel cell, and why the hydrogen economy will be penetrating everyone's life during the next decade.--From publisher description.
Includes index.
0
Includes bibliographical references and index.
Keywords: Fuel cells